The Effect of Thermal Annealing on Mechanical and Optical Properties of MgAl2O4 Ceramics Fabricated by Spark Plasma Sintering; Russian Physics Journal; Vol. 67, No. 4 - Deulina D. E. Darjya Evgenjevna; Paygin V. D. Vladimir Denisovich; Shevchenko I. N. Ivan Nikolaevich; Stepanov S. A. Sergey Aleksandrovich; Dvilis E. S. Edgar Sergeevich; Khasanov O. L. Oleg Leonidovich; Valiev D. T. Damir Talgatovich; Huang Fuli (2024, 2024)
Title screen